Memberitakan Injil Tanpa Upah berdasarkan 1 Korintus 9:18 bagi Pelayanan Hamba Tuhan - Yohanes Telaumbanua (Jurnal Arrabona, 2023)
Serving God is a special calling for everyone. The response to the call is strongly influenced by the motivation of each individual. The motivation possessed by a person determines the goals to be achieved while serving. It cannot be denied that in this demanding era, every servant of God has a competitive lifestyle, namely: not wanting to be difficult, not wanting to be out of date. The motivation possessed by a person determines the goals to be achieved while serving. then the ministry of God's servant changed direction and motivation to serve. To overcome this problem, the author raises a Bible character named Paul, who is so persistent in serving God, that he says "I preach the gospel without reward" I Corinthians 9:18. The context is close to the text of verses 15-18, where Paul explains his rights to everyone at that time. In verse 12 Paul compares himself to other ministries that have the right to work, even though Paul already has a Climax of thought and calling as written in 1 Corinthians 9:18, The writer uses descriptive exegetical-qualitative method. Where the author will provide the correct interpretation of the preaching of the gospel as a reward for the results of exegesis. Thus answering the misunderstanding of the meaning of wages in service. So that God's servants get a new understanding of merit and return to serve God with pure motivation. The author concludes that it is very important for every servant of God to purify his motivation in serving, so that true, pure ministry is created in carrying out noble responsibilities, namely preaching the Gospel to everyone. our reward comes from God. Keep in mind, the wrong motivation in serving will damage the ministry.   Melayani Tuhan merupakan panggilan khusus bagi setiap orang. Respon terhadap panggilan tersebut sangat dipengaruhi oleh motivasi masing-masing individu. Motivasi yang dimiliki oleh seseorang menentukan tujuan yang akan dicapainya selama mengabdi. Tidak dapat dipungkiri bahwa di zaman yang serba menuntut ini, terdapat gaya hidup kompetitif yang dimiliki setiap hamba Tuhan, yaitu: tidak mau susah, tidak mau ketinggalan zaman. Motivasi yang dimiliki oleh seseorang menentukan tujuan yang akan dicapainya selama mengabdi. kemudian pelayanan hamba Tuhan berubah arah dan motivasi melayani. Untuk mengatasi permasalahan tersebut, penulis mengangkat tokoh Alkitab yang bernama Paulus, yang betapa gigihnya ia dalam melayani Tuhan, hingga ia berkata “Aku memberitakan Injil tanpa upah” I Korintus 9:18. Konteks dekat dengan teks dari ayat 15-18, dimana Paulus menjelaskan hak-haknya kepada semua orang pada saat itu. Pada ayat 12 Paulus membandingkan dirinya dengan pelayanan lain yang mempunyai hak dari pekerjaannya, walaupun demikian Paulus telah memiliki Klimaks pemikiran dan panggilannya sebagaimana yang tertulis 1 Korintus 9:18, Penulis menggunakan metode deskriptif eksegetis-kualitatif. Dimana penulis akan memberikan tafsir yang benar mengenai pemberitaan injil sebagai imbalan dari hasil eksegesis. Demikian menjawab kekeliruan pemahaman mengenai makna upah dalam pelayanan. Agar para hamba Tuhan mendapat pemahaman baru tentang pahala dan kembali mengabdi kepada Tuhan dengan motivasi yang murni. Penulis menyimpulkan bahwa sangat penting bagi setiap hamba Tuhan untuk menyucikan motivasinya dalam melayani, sehingga tercipta pelayanan yang sejati, murni dalam melakukan tanggungjawab yang mulia, yaitu pemberitaan Injil kepada semua orang. pahala kita berasal dari Tuhan. Perlu di ingat, motivasi yang salah dalam melayani akan merusak pelayanan.